Safety profile and surgical outcomes of early vitrectomy in eyes with unexplained fundus-obscuring vitreous haemorrhage - Flores-Sánchez, Blanca C.; Bloch, Edward; Sanghi, Priyanka; da Cruz, Lyndon (Eye (London), 2023)
Objectives To investigate the safety profile and the surgical outcomes in a large cohort of subjects undergoing early vitrectomy for unexplained fundus-obscuring vitreous haemorrhage (FOVH). Methods Retrospective, single-centre case series of 186 consecutive eyes presenting between January 2018 and February 2020. Primary outcomes included change in best-corrected visual acuity (BCVA), rate of intra-operative retinal tears or retinal detachment (RD), baseline proliferative vitreoretinopathy (PVR), association of demographics with clinical outcomes, and rate of significant adverse events characterised by reoperation. Results Main final diagnosis was haemorrhagic posterior vitreous detachment (76%) and the overall risk of a retinal tear with or without RD found at the time of surgery was 69%. Vitrectomy was completed within 24 h in 94% of eyes. Rate of RD was 18%; all cases were macula-sparing with no PVR. Mean change in BCVA from baseline to final follow-up was −1.53 ± 0.69 LogMAR, p < 0.001. Time from presentation to surgery was significantly associated with final BCVA ( p = 0.036, beta co-efficient 0.097). There was a significant association between presence of RD and age <60 y (OR 0.94, 95%CI [0.90–0.98], p = 0.003). 4.8% required repeated vitrectomy for post-operative RD (4), epiretinal membrane formation (3), removal of oil (1), and recurrent FOVH (1). None of these reoperations were induced by complications during the first surgery. Conclusion There is a high rate of retinal breaks in cases with unexplained FOVH, and the risk of a concomitant RD is higher in younger subjects. Early vitrectomy within 24 h appears a safe first-line treatment and yields good clinical outcomes.